2012
DOI: 10.1137/10082364x
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Variants of Block Restarted GMRES Methods with Application to Geophysics

Abstract: In a wide number of applications in computational science and engineering the solution of large linear systems of equations with several right-hand sides given at once is required. Direct methods based on Gaussian elimination are known to be especially appealing in that setting. Nevertheless when the dimension of the problem is very large, preconditioned block Krylov space solvers are often considered as the method of choice. The purpose of this paper is thus to present iterative methods based on block restart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…The new iterate is optimal in this subspace in the minimum residual least-squares sense. We mention that Calandra et al [7] have recently described a block version of FGMRES which-while sharing some similarities with the work described here-differs both in scope and details with the GMRES algorithm with multiple preconditioners we propose.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The new iterate is optimal in this subspace in the minimum residual least-squares sense. We mention that Calandra et al [7] have recently described a block version of FGMRES which-while sharing some similarities with the work described here-differs both in scope and details with the GMRES algorithm with multiple preconditioners we propose.…”
mentioning
confidence: 56%
“…It was studied, e.g., in [9], [25], [34], [45], and applied recently, e.g., in [7]; see also [18] and references therein. We also mention block Arnoldi as a necessary important ingredient; see, e.g., [40], [41], [38, §6.12].…”
Section: Derivation Of Mpgmresmentioning
confidence: 99%
“…A first study of the Block GMRES was proposed in the thesis of Vital [33], followed by new theoretical results [17]. Plenty of applications of these methods have been proposed since then [34], [35], mainly for the simulation of wave propagation phenomena [36], [37] or lattice quantum chromodynamics [38] with multiple sources. Since each of these sources may yield a different right-hand side, efficient block methods are needed to handle demanding simulations with sequences of tall and skinny right-hand sides B i .…”
Section: B Block Iterative Methodsmentioning
confidence: 99%
“…Due to their indefiniteness, these systems are known to be very challenging for iterative methods [18]. Based on previous studies [11,12,26], we consider a recently proposed block flexible Krylov subspace method (BFGMRES-S [11, Algorithm 3]) for the solution of the linear system with multiple right-hand sides (2). In [11] the authors have shown the relevance of the BFGMRES-S algorithm combined with a variable two-level preconditioner to address the solution of such large-scale acoustic forward problems in a distributed memory parallel environment.…”
Section: The Forward Problemmentioning
confidence: 99%
“…We refer the reader to [12,Algorithm 5] for a complete description of the geometric two-grid preconditioner and to [33] for additional theoretical properties in relation with Krylov subspace methods. Applications to large-scale forward acoustic problems have been considered in detail in [26,Chapter 4].…”
Section: The Forward Problemmentioning
confidence: 99%